The Influence of Service Quality, Price, and Electronic Word of Mouth on Visit Intention - Syaharani, Rosalina Putri; Juliati, Ratih; Hilmi, Luqman Dzul (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The purpose of this study was to examine and analyze the effect of Service Quality, Price, and Electronic Word of Mouth on Visit Intention (a study of potential tourists at Selecta Recreation Park). The population in this study was someone who had never visited Selecta Recreation Park, with a sample of 200 respondents. The characteristics of the respondents are prospective tourists who are in Malang Raya and have never visited Selecta Recreation Park but know Selecta Recreation Park from Social Media Instagram, aged 17-40 years. The sampling technique uses purposive sampling. This research was conducted from June to July 2023 by distributing online questionnaires via Google Form. Data analysis techniques using multiple linear regression, t test, and dominant test. The results of this study conclude that Service Quality, Price, and Electronic Word of Mouth (E-WOM) have a positive and significant effect on Visit Intention. E-WOM has a dominant influence on Visit Intention.